2017
DOI: 10.1017/s0007114517003063
|View full text |Cite
|
Sign up to set email alerts
|

Dietary phosphatidylcholine impacts on growth performance and lipid metabolism in adult Genetically Improved Farmed Tilapia (GIFT) strain of Nile tilapiaOreochromis niloticus

Abstract: This study aimed to determine the effects of supplementing the diet of adult Nile tilapia Oreochromis niloticus with phosphatidylcholine (PC) on growth performance, body composition, fatty acid composition and gene expression. Genetically Improved Farmed Tilapia fish with an initial body weight of 83·1 (sd 2·9) g were divided into six groups. Each group was hand-fed a semi-purified diet containing 1·7 (control diet), 4·0, 6·5, 11·5, 21·3 or 41·0 g PC/kg diet for 68 d. Supplemental PC improved the feed efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…Recently, Apraku et al (2019) found that dietary substitution of FO with other sources as coconut and corn oil increased LPL and FAS enzyme activity in tilapia muscle with no difference in their activity in the liver.Lecithin supplementation increased LPL and FAS mRNA expression, with the highest expression observed in fish reared on a plantbased diet. Partially consistent with these results,Tian et al (2017)…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Recently, Apraku et al (2019) found that dietary substitution of FO with other sources as coconut and corn oil increased LPL and FAS enzyme activity in tilapia muscle with no difference in their activity in the liver.Lecithin supplementation increased LPL and FAS mRNA expression, with the highest expression observed in fish reared on a plantbased diet. Partially consistent with these results,Tian et al (2017)…”
supporting
confidence: 79%
“…On the other hand, relative mRNA levels of these genes were significantly increased in fish supplemented with lecithin, suggesting that lecithin has a stimulatory effect on their expression resulting in enhanced growth, especially in fish reared on a plant-based diet. In contrast and regardless of dietary composition, Tian et al (2017) found that expression levels of the growth hormone in the brain and IGF in liver tissue were reduced by increasing phosphatidylcholine levels in the tilapia diet.…”
Section: Growth-and Lipid Metabolism-regulating Genes Expressionmentioning
confidence: 83%
See 1 more Smart Citation
“…PE is one of the components of the cell membrane system, and the majority of PE is located in the inner lipid bilayer structure [ 40 ]. A recent study showed that PC could increase the expression of LPL and hormone-sensitive lipase and decrease the FAS expression in the liver of tilapia [ 41 ]. PE is required for the function and integrity of mitochondrial membranes [ 34 ] and is used to help TC metabolism by transforming into PC [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Abdel-Ghany et al [ 74 ] observed that cold shock to Nile tilapia can enhance cold tolerance by reducing the changes in systemic saturated fatty acids and increasing the lipid metabolism of n-6 and n-3 unsaturated fatty acids. Additionally, Li et al [ 75 ] determined that in tilapia diets supplemented with arginine, the regulation of lipid metabolism-related genes can reduce the mechanism of liver fat deposition and fatty acid composition induced by a high-fat diet [ 76 ]. From the transcript sequencing results of this study, it was observed that the arginine kinase gene of the cold-tolerant strain possessed high expression levels.…”
Section: Discussionmentioning
confidence: 99%